The effects of noncontingent reinforcement on task disengagement following failure of differential reinforcement treatment. (17th October 2022) - O'Brien, Matthew J.; Romani, Patrick W.; Berg, Wendy K.; Wacker, David P.
Abstract: Following the failure of applications of differential reinforcement (DR), the effects of reinforcement delivered noncontingently (NCR) on task disengagement and task completion were evaluated within reversal designs for three children with autism spectrum disorder. In Experiment 1, we compared DR and NCR schedules that combined positive and negative reinforcement. In Experiment 2, we replicated the results of Experiment 1 and then evaluated NCR schedules composed solely of negative reinforcement and NCR schedules that combined negative reinforcement with high‐or low‐preferred stimuli. In Experiment 3, we further analyzed NCR schedules that included different types and qualities of positive reinforcement, but without the inclusion of negative reinforcement. The results showed that NCR schedules using positive reinforcers can be effective as a treatment for task disengagement, but the type and preference of the reinforcer can alter effectiveness. These results are interpreted in terms of the motivating operations associated with task disengagement.